Perspectivas acerca de la actividad editorial y de revisión por pares de los investigadores peruanos en odontología - Quispe-Salcedo, Angela (2023)
Since the establishment of new strategies for the promotion of academic research activity in public and private higher education institutions, driven by the declaration of Peruvian University Law 30220 in 2014, scientific production in dental research have progressively increased in our country. As shown by a recent bibliographic study on the scientific production of Peruvian Dental Schools from 2014 to 2019 after the enactment of this law, all public and private schools notably increased their contributions, being three institutions: Peruvian University Cayetano Heredia- School of Dentistry, National University of San Marcos Faculty of Dentistry, and Cientifica del Sur University School of Stomatology, the highest scoring in the SCOPUS scientific database